The Civil Liability Arising from Affective Abandonment - Santos, Ednaiara de Almeida Dias dos (2023)
This research addresses civil liability in the context of Family Law with a focus on emotional abandonment. It begins with an introduction to law, highlighting its duality between legal norms and principles, and its connection with ethics and morals. Next, the research explores contemporary law and how civil liability is undergoing a new paradigm. The articles of the 2002 Civil Code that deal with civil liability are presented, defining it as the obligation to repair damage caused by an unlawful act, in addition to highlighting that civil liability is not limited to the Law of Obligations, but also extends to other legal institutes, such as Family Law. In relation to emotional abandonment, the research discusses the transformations in family relationships throughout history, highlighting the change in the filiation criterion from consanguinity to affection and emphasizing the duty of parents to offer affection and care to their children, regardless of the love between them. , and the lack of these elements is characterized as emotional abandonment and highlights that there can be serious consequences for children and adolescents, and cites the Federal Constitution and the Statute of Children and Adolescents to reinforce the obligation of parents in relation to care and coexistence with their children children. Civil liability arising from emotional abandonment is explained as the obligation to repair the emotional damage caused and it is emphasized that it falls under subjective civil liability, and that the presence of damage is crucial for repair. The objective is to analyze case law to illustrate situations in which emotional abandonment may or may not constitute compensable damage, highlighting the importance of evaluating each case individually. Finally, the research concludes that civil liability in the context of emotional abandonment is a way of repairing the emotional damage caused, being a means of promoting the dignity of the human person and the best interests of children and adolescents.